Synergistic degradation of waste agricultural plastic film in supercritical water-CO2 mixed fluid with high CO2 concentration: Gasification characteristics and reaction pathways - Bin Bai; Xinyue Yu; Chen Fu; Hong Song; Qinpei Nie; Hui Jin (Fuel, 2027)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

A synergistic enzymatic strategy for comprehensive improvement of bread quality and digestibility using a novel maltohexaose-forming amylase and a 4,6-α-glucanotransferase - Yu-chuan Wang; Hong Liu; Li-xiao Fu; Meng-jun Han; Qiao-juan Yan; Zheng-qiang Jiang; Yan-xiao Li (Food Hydrocolloids, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Toward a sustainable biorefinery of intestinal mucosa: Green extraction of heparin and valorization of co-products rich in glycosaminoglycans and bioactive peptides - Zetao Wang; Hong Lv; Zhongquan Zhao; Yongju Zhao; Yu Fu; Wei Wu (Trends in Food Science & Technology, 2026)

Integrative taxonomic revision of Uropsilus (Uropsilinae, Talpidae) combining genomic, morphological and geographic evidence - Yi-Xian Li; Quan Li; Wen-Yu Song; Xue-You Li; Kenneth Otieno Onditi; Xiao-Xin Pei; Hong-Jiao Wang; Chang-Kun Fu; Shao-Ying Liu; Zhong-Zheng Chen; Xue-Long Jiang (Molecular Phylogenetics and Evolution, 2026)

Physicochemical pretreatment for enhancing anammox and related coupled processes in the treatment of high-strength ammonium industrial wastewater: Research advances and prospects - Long Jiao; Xue-chao Wang; Jia-lin Xue; Zhuo-yuan You; Jie Li; Jia-jun Fu; Hong Yu (Journal of Environmental Chemical Engineering, 2026)

Synergistic vacuum steam pulse blanching and gliding arc cold plasma pretreatment enhances drying efficiency and folate retention in Yardlong bean pods - Samuel Ariyo Okaiyeto; Fan Yang; Dan Liu; Lei Fu; Shi-Han Yu; Xiao-Xiao Niu; Feng-Lun Zhang; Cheng Zhang; Feng-Kui Xiong; Mohsen Mokhtarian; Weiqiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Biocontrol mechanism of Streptomyces sp. MEPF0303 against Sclerotium delphinii causing Dendrobium officinale southern blight revealed by multi-omics analysis - Qiao Liu; Yu-Jie Chen; Jing Shi; Yong-Jing Zhang; Hai-Lan Fu; Zi-Ling Tao; Tao Zhou; Zhi-wu Tan; Ji-Luan Zhang; Ji-Hong Jiang; Lu-Dan Li (Pesticide Biochemistry and Physiology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Enzyme-specific release dynamics of umami and bitter peptides from shrimp processing by-products: a machine learning-aided study - Jiasi Li; Jiayuan Chen; Hong Lv; Soottawat Benjakul; Yuhao Zhang; Yu Fu (Food Chemistry, 2026)

A flexible piezoresistive pressure sensor with an interlocking microstructure based on modulated corona electric field - Chenghang Yu; Jian Xu; Fu Lv; Bing Liu; Juan Li; Xin Li; Zijian Hong; Yongjun Wu; Yuhui Huang (Chemical Engineering Journal, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

Fat on Fire: Disrupted Microglial Lipid Metabolism as a Driver of Anesthetic Neurotoxicity - Yu-Jie Mou; Hai-Yue Tu; Yi-Chan Wang; Shao-Yong Song; Hua-Yue Liu; Dong Wang; Jun-Chao Wu; Xiao-Wen Meng; Zheng-Hong Qin; Fu-Hai Ji (Neuroscience Bulletin, 2026)

Calculating Receptor Occupancy using TMDD Models – What has to be Considered? - Yu Fu; Liang Yang; Hong Su; Ye Yao; Yu Li; Peiming Ma (The AAPS Journal, 2026)

Maximum mean discrepancy enhanced Informer for accurate cross-domain dual-timescale effluent prediction in wastewater treatment plants - Jun-Hong Zhou; Yang-Guang Xia; Xiao-Li Yang; Xin-Yi Xiang; Yu-Jia Fu (Bioresource Technology, 2026)

Influence of LED lighting on the cell growth, accumulation of bioactive flavonoids and terpenoids, antioxidant response, and photoreceptor-mediated light signal transduction in Ginkgo biloba L. callus cultures - Qing-Yan Gai; Jiao Jiao; Yu-Jie Fu; Hong-Yan Zhao; Xiao-Qing Wang; Dan Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Microscopic Hydraulic–Mechanical Coupling Fracturing Behavior and Failure Mechanisms of Reservoir Rocks - Zhi Zhao; Zhi-Hong Li; Yun-Gang Duan; Liang-Fu Xie; Zheng Li; Guo-Feng Yu; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2026)

A review of antibiotic treatment by bioelectrochemical systems: Degradation mechanisms, resistance gene control, and hybrid technologies - Hexing Li; Hong-Yu Ren; Qiang Fu; Tianxiao Li; Fanying Kong (Process Safety and Environmental Protection, 2026)

Hurdle strategies based on high-pressure processing, ultrasonication and pulsed electric field for shelf life extension of refrigerated Asian green mussel - Suriya Palamae; Natchaphol Buamard; Watcharapol Suyapoh; Bin Zhang; Yu Fu; Hui Hong; Soottawat Benjakul (Food Control, 2026)

Wide range lower atmosphere duct parameter inversion from automatic identification system signals using hybrid strategy artificial lemming algorithm - Ting Ting Fu; Hao Cha; Yu Luo; Hong Wei Fu; Yu Zhang; Bin Tian (Frontiers in Marine Science, 2026)
Lower atmospheric ducts significantly alter the propagation of Very High Frequency (VHF) and higher-frequency electromagnetic waves in the marine boundary layer, critically impacting radar and communication systems. Effective duct monitoring is essential for optimizing these systems. Emerging, more economical remote sensing approaches—such as satellite-based remote sensing and the monitoring of ubiquitous shipborne Automatic Identification System (AIS) signals—provide promising alternatives for large-scale, cost-effective data acquisition compared to the traditional monitoring methods (e.g., radiosondes, lidars). To tackle the challenges posed by the inversion of lower-atmospheric duct with large vertical extent and high parameter dimensionality, robust and accurate parameter inversion techniques are urgently required. To address this, this study proposes the Hybrid Strategy Artificial Lemming Algorithm (HSALA), an intelligent optimization framework for prior-information-free duct inversion. Comparative inversion simulations of HSALA, the standard Artificial Lemming Algorithm (ALA), Particle Swarm Optimization (PSO), Grey Wolf Optimization (GWO), and Harris Hawk Optimization (HHO) demonstrate HSALA’s superior accuracy and stability under ideal, noise-free conditions. It achieves a mean inversion accuracy exceeding 98% and reduces the root mean square error (RMSE) by over 80% on average in noise-free conditions across 30 trials. Further validation using field-collected AIS data yields a mean parameter inversion accuracy of approximately 81.4%, confirming the method’s practical applicability while highlighting the performance gap introduced by real-world complexities such as signal noise, model bias and atmospheric horizontal inhomogeneity. This method provides a promising and effective solution for operational duct monitoring using AIS signals, bridging a significant gap toward real-time, large-range inversion. The insights from the field validation underscore the value of this approach for engineering practice and outline a clear path for future refinement.

A novel endophytic fungus Fusarium oxysporum G-07 exhibits antagonism against Rhizoctonia solani and promotes growth in Scutellaria baicalensis - Xiao-Qing Wang; Jiao Jiao; Qing-Yan Gai; Jin-Xian Fu; Yu-Jie Fu; Hong-Yan Zhao; Ying Liu (Pesticide Biochemistry and Physiology, 2026)

Insights into microscopic mechanisms of quaternary ammonium rosin-based amide resin in removing hexose alkaline degradation pigments - Xiao-Song Tang; Wei Wei; Yan-Hong Wei; Yu-Huan Lu; Xiang-Yi Tang; Wen Li; Fu-Hou Lei (Journal of Environmental Chemical Engineering, 2026)

Development of a sporopollenin-hydrogel-Cu2O composite for dye removal: Addressing the dual challenges of agglomeration and ‌embedding of metal nanoparticles in hydrogel-based catalysts - Ying Liu; Jiao Jiao; Qing-Yan Gai; Yi-Bo Qiu; Hong-Yan Zhao; Xiao-Qing Wang; Yu-Jie Fu (Journal of Environmental Sciences, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Hydraulic retention time extension and multi-point reflux promote full-scale partial mainstream anaerobic ammonium oxidation (Anammox) at low temperatures - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Wen-Bo Liang; Yu-Jia Fu (Chemical Engineering Journal, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

In-situ constructed organic-copper bilayer SEI for exceptional cycling stability of Zn anodes - Jingwen Liu; Xinghui Liu; Teng Yu; Meiting Fu; Yibo Ma; Wenxiang Sun; Zhen Hong; Tianyi Ma; Lei Wang; Caixia Li (Chemical Engineering Journal, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Diclofop-methyl resistance conferred by LrGSTU181 overexpression in Lolium rigidum - Hong Qian; Yalin Zeng; Hui Zhao; Mingrui Fu; Qin Yu; Lang Pan (Pesticide Biochemistry and Physiology, 2026)

Quercetin alleviates Deoxynivalenol-induced myocardial fibrosis in chicken by regulating MCU-mediated mitochondrial calcium overload - Hong-yu Fu; Yi Fang; Jia Chen; Hongxue Yang; Xuehan Jiang; Yishan Yin; Bo Li; Xiaoxiao Chen; Jingzeng Cai; Ziwei Zhang (Journal of Hazardous Materials, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

A systematic review for degradation of tetracycline antibiotics by microbial fuel cells: Performance, mechanisms, microbial community and coupled system - Jiayi Li; Hong-Yu Ren; Qiang Fu; Tianxiao Li; Fanying Kong (Process Safety and Environmental Protection, 2025)

Pathogenic and beneficial microbial communities determine the shelf life of stored 'Fengtangli' plums - Yu-Ru Wang; Tomislav Cernava; Shi-Xian Zeng; Hong Chen; Feng-Quan Liu; Zheng-Qing Fu; Tao Zhou; Yong Wang; Jia Liu (Postharvest Biology and Technology, 2025)

Multigraph fusion neural network for predicting available cadmium levels in farmland soils - Ren-Jie Zhang; Shu-Fang Pan; Huai-Zeng Xing; Tian-Hao Dong; Sai-Hua Liu; Tao Xue; Fa-Xiang Tian; Hong-Yu Fu; Yun-He Xie; Xiong-Hui Ji (Environmental Pollution, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Harnessing nanochaperone-triggered ferritinophagy for targeted protein degradation and breast cancer therapy - Xiaoling Xu; Qingqing Dong; Yutong Zhao; Jun Yang; Keda Yang; Peifen Fu; Hong Yu; Xiaoyuan Chen; Longguang Tang; Wei Chen (Chemical Engineering Journal, 2025)

Upcycling shrimp processing by-products into dual-functional peptides: Insights into bioactivity and flavor - Jiayuan Chen; Hong Lv; Jiasi Li; Qiang Zhang; Soottawat Benjakul; Yuhao Zhang; Yu Fu (Food Chemistry, 2025)

Regulation of peptide hydrophobicity by self-assembly of casein peptides with ferulic acid to potentially reduce peptide bitterness and improve in vitro digestive activity - Si-Yi Han; Hong-Fu Zhao; Bo-Kang Yu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

Mitochondrial DNA leakage and micronucleus formation activate the cGAS–STING pathway in aristolochic acid I-induced nephritis - Yu yang Lei; Yu shi Hu; Yi yi Cao; Jing Xi; Yu ning Ma; Xiao hong Zhang; Qin wen Gao; Ji an Fu; Xin yu Zhang; Li Su; Yang Luan (Food and Chemical Toxicology, 2025)

Performance optimization and microbial community analysis of integrated anaerobic BES-aerobic MBBR system for azo dye treatment with related wastewater remediation - Fanying Kong; Qiang Fu; Lihong Wang; Hong-Yu Ren (Chemical Engineering Journal, 2025)

Evaluating the ecological and agricultural benefits of intelligent sustainable green energy floating gardens: impacts on microorganisms and vegetable growth - Yuan-Hsiou Chang; Hsiao-ling Lu; Tsai-Fu Chuang; Hong-Bin Lai; Yi-Zhen Yu (Environmental Science and Pollution Research, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Degradation of mesotrione in bioelectrochemical system: Performance, mechanisms, and microbial communities - Zhibing Xing; Qiang Fu; Hong-Yu Ren; Lihong Wang; Fanying Kong (Chemical Engineering Journal, 2025)

Correction to: Overexpression of Tau Rescues Nogo-66-Induced Neurite Outgrowth Inhibition In Vitro - Yu-Chao Zuo; Hong-Lian Li; Nan-Xiang Xiong; Jian-Ying Shen; Yi-Zhi Huang; Peng Fu; Hong-Yang Zhao (Neuroscience Bulletin, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Mass spectrometry imaging unveils the fate of azithromycin in zebrafish: Uptake, distribution, transformation, and metabolic impact - Hang Fu; Leiyi Ji; Yanxiao Jiang; Changjun Yu; Hong Zhang; Guangfeng Kan; Jie Jiang (Journal of Environmental Chemical Engineering, 2025)

Z-scheme MIL-88A(Fe)/LaFeO3 heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced organic pollutant detoxification - Ruo-Xuan Mei; Peng Wang; Fu-Xue Wang; Zi-Chen Zhang; Xiao-Hong Yi; Zi-Yu Jia; Ke-Xin Li; Chong-Chen Wang (Environmental Research, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

An improved direct analysis method of transmission towers incorporating geometric defects and bolt slippage effects - Yu Zhu; Hong-Nan Li; Xing Fu; Jia-Xiang Li; Rui-Zeng Wei (Engineering Structures, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

The nuclear receptor gene SfE75 regulates the molting of Sogatella furcifera - Yi-Ming Wang; Yan-Yu Wang; Ming-Fu Gong; Shi-Yan Zhang; Jiang-Ling Chen; Xin Li; Cao Zhou; Hong Yang (Journal of Asia-Pacific Entomology, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Development and evaluation of 50 K liquid SNP array for blunt snout bream (Megalobrama amblycephala) - Li-Fei Luo; Yao Wang; Shi-Long Wang; Yue Yu; Yu-Ye Fu; Chun-Hong Nie; De-Wen Tang; Ze-Xia Gao (Aquaculture, 2025)

Physiological and proteomic insights into silver nanoparticle-induced stress responses and resistance mechanisms in aerobic denitrifying Enterobacter cloacae HNR - Teng-Fei Ma; Hong-Xi Ma; Chong-Yang Xing; Hui-Min Fu; Yu Shen; You-Peng Chen; Xiang-Yang Wei (Journal of Environmental Chemical Engineering, 2025)

Decoding nattokinase efficacy: From digestion and absorption to lipid pathway modulation in high-fat diet-induced atherosclerosis - Yongjie Zhou; Zixin Fu; Peipei Dou; Chen Yu; Xianyou Dong; Hui Hong; Yongkang Luo; Yuqing Tan (Food Bioscience, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mechanistic impact of Gracilaria bailinae extracts on photosynthesis and metabolism in Phaeodactylum tricornutum - Li-Gong Zou; Fu-Fang Wen; Xiao Zhang; Gang Li; Qing Wang; Hong-Ye Li; Yu-Feng Yang (Marine Environmental Research, 2025)

Enhancement of antibacterial activity of cinnamaldehyde against Bacillus cereus by nanoemulsion and its application in milk - Rui Cui; Fu-Yu Liu; Hong Wu (Food Bioscience, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

A specific GAGTT insertion/deletion variation in the IL-10 gene promoter alters the disease resistance of grass carp - Hong Yang; Jiaojiao Fu; Mengyuan Zhang; Xinyi Cao; Yu Xiao; Hongquan Wang; Tiaoyi Xiao; Zhao Lv (Aquaculture, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Inhibition of CB1R in the Hypothalamic Paraventricular Nucleus Ameliorates Hypertension Through Wnt/β-Catenin/RAS Pathway - Hong-Li Gao; Yu Yang; Hua Tian; Li-Yan Fu; Kai-Li Liu; Xiu-Yue Jia; Xiao-Lian Shi; Yu-Ming Kang; Xiao-Jing Yu (Cardiovascular Toxicology, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

The role of deep learning in aortic aneurysm segmentation and detection from CT scans: A systematic review and meta-analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Next Research, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Thalassospira aquimaris sp. nov. and Winogradskyella marincola sp. nov. two marine bacteria isolated from an agar-degrading co-culture - Zi-Yue Fu; Dao-Feng Zhang; Meng-Han Huang; Hong-Chuan Wang; Xiao-Ye Chen; Yu-Fang Yao; Yang Yuan; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Dual zinco-phobic/-philic ferroelectric nanorods coated mesh for stable Zn anode - Jingwen Ma; Weishen Liu; Bo Fu; Jingji Zhang; Quan Zong; Huiwei Du; Tao Hong; Huanan Yu; Yongchun Ye; Jiangying Wang; Haijiao Xie (Chemical Engineering Journal, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Gut microbiota dynamics in KK-Ay mice: restoration following antibiotic treatment - Jinni Hong; Tingting Fu; Weizhen Liu; Miao Yu; Yanshan Lin; Cunyun Min; Datao Lin (Folia Microbiologica, 2024)

Norfloxacin affects inorganic nitrogen compound transformation in tailwater containing Corbicula fluminea - Junling Wei; Zijin Hong; Wei Li; Xiufang Yang; Zihao Fu; Xinyu Chen; Junxiang Hu; Zhangnan Jin; Bojiang Long; Xuexiu Chang; Yu Qian (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Antibiotics ingestion altered the composition of gut microbes and affected the development and reproduction of the fall armyworm - Yan Fu; Luo-Yan Zhang; Qing-Yi Zhao; Da-Ying Fu; Hong Yu; Jin Xu; Song Yang (Journal of Pest Science, 2024)

Biomechanical behavior of grass roots at different gauge lengths - Jiangtao Fu; Zhe Zhou; Hong Guo; Jimei Zhao; Dongmei Yu; Jie Wu; Xiasong Hu (Journal of Mountain Science, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Deep Learning Models for Aorta Segmentation in Computed Tomography Images: A Systematic Review And Meta-Analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Kuan-Ting Wu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Journal of Medical and Biological Engineering, 2024)
Purpose This systematic review and meta-analysis was conducted to evaluate the usefulness of deep learning (DL) models for aorta segmentation in computed tomography (CT) images. Methods Adhering to 2020 PRISMA guidelines, we systematically searched PubMed, Embase, and Web of Science for studies published up to March 13, 2024, that used DL models for aorta segmentation in adults’ chest CT images. We excluded studies that did not use DL models, involved nonhuman subjects or aortic diseases (aneurysms and dissections), or lacked essential data for meta-analysis. Segmentation performance was evaluated primarily in terms of Dice scores. Subgroup analyses were performed to identify variations related to geographical location and methodology. Results Our review of 16 studies indicated that DL models achieve high segmentation accuracy, with a pooled Dice score of 96%. We further noted geographical variations in model performance but no significant publication bias, according to the Egger test. Conclusion DL models facilitate aorta segmentation in CT images, and they can therefore guide accurate, efficient, and standardized diagnosis and treatment planning for cardiovascular diseases. Future studies should address the current challenges to enhance model generalizability and evaluate clinical benefits and thus expand the application of DL models in clinical practice.

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Floating MIL-88A(Fe)@expanded perlites catalyst for continuous photo-Fenton degradation toward tetracyclines under artificial light and real solar light - Guang-Chi Liu; Xiao-Hong Yi; Hong-Yu Chu; Chong-Chen Wang; Ya Gao; Fei Wang; Fu-Xue Wang; Peng Wang; Jian-Feng Wang (Journal of Hazardous Materials, 2024)

Combined multi-omics approach to analyze the flavor characteristics and formation mechanism of gabaron green tea - Dongzhu Huang; Dongqiao Zheng; Chenyi Sun; Maoyin Fu; Yuhan Wu; Hong Wang; Jieyao Yu; Yunqiu Yang; Yeyun Li; Xiaochun Wan; Qi Chen (Food Chemistry, 2024)

Hyaluronic acid-based injectable formulation developed to mitigate metastasis and radiation-induced skin fibrosis in breast cancer treatment - Yu-Chi Wang; Pei-Wei Shueng; Chan-Yu Hu; Fu-I Tung; Ming-Hong Chen; Tse-Ying Liu (Carbohydrate Polymers, 2024)

Toxic Metal Soil Speciation, Corn Accumulation and Health Risk Assessment in Acidic red soil Farmland in Mineral Industry Area - Yu Qian; Xiaoqi Li; Jie Yang; Rui Zhou; Zijin Hong; Change Liu; Shiyu Li; Yonggui Zhao; Denggao Fu; Ying Pan; Huan Feng; Marek Kolenčík; et al. (Water, Air, & Soil Pollution, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Efficiency and mechanism of enhanced norfloxacin removal using amorphous TiO2-modified biochar - Yu-liang Hu; Ying Liu; Weng Fu; Hong Yang (Environmental Pollution, 2024)

Tanshinone IIA is superior to paricalcitol in ameliorating tubulointerstitial fibrosis through regulation of VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy - Jing-Yi Zeng; Yu Wang; Fu-Yuan Hong; Miao Miao; Yu-Ying Jiang; Zi-Xuan Qiao; Yun-Tao Wang; Xiao-Rong Bao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Glomerulosclerosis and tubulointerstitial fibrosis (TIF) are closely involved in the development of diabetic nephropathy (DN). Moreover, the development of TIF is closely related to epithelial-to-mesenchymal transition (EMT). Tanshinone IIA (Tan) has various pharmacological effects, especially the anti-fibrotic effect. And it is mainly used in the clinical treatment of cardiovascular diseases. Currently, the protective effect of Tan on DN and its possible mechanism have not been clearly elucidated. Our previous studies illustrated that Tan could improve the EMT of HK-2 cells induced by high glucose by regulating the vitamin D receptor (VDR)/Wnt/β-catenin pathway. Here, we collected demographic information and laboratory results from the National Health and Nutrition Examination Survey (NHANES) database in order to investigate the relationship between VD and DN. Then, we established a DN model and treated DN rats with Tan and paricalcitol (Par) for 6 weeks. We subsequently compared the changes in general condition, renal function, pathological changes, and TIF-related protein expression levels of control rats, DN rats induced by STZ, DN rats with Tan at 5.4 mg/kg, DN rats with Tan at 10.8 mg/kg, and DN rats with Par at 0.054 µg/kg, to explore the effect and mechanism of Tan and Par on DN rats. The results showed that VD had a protective effect against DN in diabetic patients. And we found that Tan had a protective effect on renal fibrosis in DN rats, which was superior to Par in improving the symptoms of “three more and one less,” reducing fasting blood glucose level, improving renal index, BUN/SCr, and UACR, reducing histopathological damage of kidney, and improving the expression of fibrosis-related proteins in kidney tissue by regulating VDR/Wnt/β-catenin pathway. Tan was superior to Par in ameliorating tubulointerstitial fibrosis by regulating VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy.

Damage constitutive model for soft rocks and its experimental verification on silty mudstone considering cyclic rock‒water interactions - Xiao-Wei Yu; Hong-Yuan Fu; Ling Zeng; Jie Liu; Xing-Yu Qiu (Bulletin of Engineering Geology and the Environment, 2024)

Immunosuppressive steroids quadrilisteroids A−C and derivatives from the terrestrial fungus Aspergillus quadrilineatus - Yu Chen; Qin Li; Yu Liang; Mengsha Wei; Hong Liao; Aimin Fu; Weiguang Sun; Chunmei Chen; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2024)

Prussian blue analogue nanospheres immobilized on self-floating biochar for micropollutant degradation via photo-Fenton process - Fu-Xue Wang; Zi-Wei Zhang; Zi-Chen Zhang; Ke-Xin Li; Ya Li; Hong-Yu Chu; Chong-Chen Wang; Jian-Feng Wang; Long Chen; Wen Liu; Hailong Wang; Peng Wang (Chemical Engineering Journal, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Cevanine-type alkaloids from the bulbs of Fritillaria unibracteata var. wabuensis and their antifibrotic activities in vitro - Lu Fu; Wenyue Tian; Meng-Yu Bao; Zhiyan Liu; Wen-Jing Ren; Jiazheng Liu; Wei Zhang; Zhifeng Zhang; Jin Gao; Li-Ping Bai; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

N-containing phenolic compounds from Periplaneta americana with triple negative breast cancer inhibitory activity - Hong-Fu Bai; Shi-Yu Zhang; Yong-Ming Yan; Yong-Xian Cheng (Phytochemistry, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Development of a full-scale flume test system for depositional behavior study of segregating tailings - Quanming Li; Zhijie Duan; Hai Shi; Yuzhen Yu; Hong Zhang; Botao Fu (Bulletin of Engineering Geology and the Environment, 2024)

Quaternary ammonium-functionalized rosin-derived resin for the high-performance capture of caramels: Experiments and quantum chemical theory simulations - Li Jiao; Wei Wei; Chun-Yu Liao; Yan-Hong Wei; Fu-Hou Lei; Wen Li (Journal of Hazardous Materials, 2024)

Simvastatin ameliorates synaptic plasticity impairment in chronic mild stress-induced depressed mice by modulating hippocampal NMDA receptor - Xu-Ben Yu; Kai-Long Zhong; Chuang Chen; Jing Fu; Fang Chen; Hong-Min Zhou; Xiu-Hua Zhang; Kwonseop Kim; Jing-Ye Pan (Psychopharmacology, 2024)

Transcriptomic analysis revealed the dynamic response mechanism to acute ammonia exposure in the ivory shell, Babylonia areolata - Xin Hong; Jie Qin; Deng Fu; Yi Yang; Aimin Wang; Zhifeng Gu; Feng Yu; Chunsheng Liu (Fish & Shellfish Immunology, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

High efficient alkaline hydrogen evolution catalyzed by W2COx-Ru composite system containing bridged oxygen - Yu Dai; Hong Chuan Fu; Xiao Hui Chen; Qing Zhang; Ting Li; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

A new coupled depth-integrated model incorporating 3D DDA on debris flow with large boulders - Pengcheng Yu; Xinyan Peng; Guangqi Chen; Haiying Fu; Yingbin Zhang; Zheng Han; Hong Zhang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Diode effects on street canyon ventilation in valley city: Temperature inversion and calm geostrophic wind - Jin Shang; Huai-Yu Zhong; Hong-Liang Zhang; Bin Li; Xiao-Xue Wang; Fu-Yun Zhao; Yuguo Li (Building and Environment, 2023)

Risk-based irrigation decision-making for the Shihmen Reservoir Irrigation District of Taiwan - Sheng-Fu Tsai; Dong-Hong Wu; Gwo-Hsing Yu; Ke-Sheng Cheng (Paddy and Water Environment, 2023)

Parallel evolution in Crassostrea oysters along the latitudinal gradient is associated with variation in multiple genes involved in adipogenesis - Wen Teng; Huiru Fu; Zhuanzhuan Li; Qian Zhang; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Molecular Ecology, 2023)
Parallel diversification provides a proper framework for studying the role of natural selection in evolution. Yet, empirical studies from ecological ‘non‐model’ species of invertebrates are limited at the whole genome level. Here, we presented a chromosome‐scale genome assembly for Crassostrea angulata and investigated the parallel genomic evolution in oysters. Specifically, we used population genomics approaches to compare two southern–northern oyster species pairs ( C . angulata – C . gigas and southern–northern C . ariakensis ) along the coast of China. The estimated divergence time of C . angulata and C . gigas is earlier than that of southern and northern C . ariakensis , which aligns with the overall elevated genome‐wide divergence. However, the southern–northern C . ariakensis F ST profile represented more extremely divergent “islands”. Combined with recent reciprocal hybridization studies, we proposed that they are currently at an early stage of speciation. These two southern–northern oyster species pairs exhibited significant repeatability in patterns of genome‐wide differentiation, especially in genomic regions with extremely high and low divergence. This suggested that divergent and purifying selection has contributed to the genomic parallelism between southern and northern latitudes. Top differentiated genomic regions shared in these two oyster species pairs contained candidate genes enriched for functions in energy metabolism, especially adipogenesis, which are closely related to reproductive behaviours. These genes might be good candidates for further investigation in vivo. In conclusion, our results suggest that similar divergent selection and shared genomic features could predictably transform standing genetic variation within one species pair into differences in another.

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

mTORC1/rpS6 and mTORC2/PKC regulate spermatogenesis through Arp3-mediated actin microfilament organization in Eriocheir sinensis - Zhen-Fang Li; Hong-Yu Qi; Jia-Ming Wang; Zhan Zhao; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Effectively removing gaseous polycyclic aromatic hydrocarbons (PAHs) by willow catkins: Do you still dislike the catkins floating? - Peng-Tuan Hu; Dong-Hai Liu; Zhi-Guo Cao; Hong Wei; Fu-Jie Zhu; Wan-Li Ma; Zi-Feng Zhang; Li-Yan Liu; Jing-Lan Feng; Yong-Feng Li; Yu-Fei Li; Yi-Fan Li (Journal of Hazardous Materials, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Coupled behaviour and strength prediction of tapered CFDST columns with large hollow ratios for wind turbine towers - Ran Deng; Xu-Hong Zhou; Wei-Dong Ji; Rong-Fu Li; Shuai-Quan Zheng; Yu-Hang Wang (Engineering Structures, 2023)

Mesomechanical characteristics of rock failure under variable amplitude cyclic loading by DEM - Ze-han Liu; Jin Yu; Chong-hong Ren; De-fu Zhu; Xiao-qin Chen (Bulletin of Engineering Geology and the Environment, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Combined effects of light pollution and vegetation height on behavior and body weight in a nocturnal rodent - Ling-Ying Shuai; Li-Qing Wang; Yang Xia; Jin-Yu Xia; Kang Hong; Ya-Nan Wu; Xin-Yi Tian; Fu-Shun Zhang (Environmental Pollution, 2023)

Fluid hydrodynamics and thermal transports in nanofluids pulsating heat pipes applied for building energy Exploitations: Experimental investigations and full numerical simulations - Wei-Wei Wang; Yong-Juan Song; Chun-Yu Zhang; Hong-Liang Zhang; Yang Cai; Fu-Yun Zhao; Jiang-Hua Guo (Energy and Buildings, 2023)

Polydopamine-modification of a magnetic composite constructed from citric acid–cross-linked cyclodextrin and graphene oxide for dye removal from waters - Qing-Di Hu; Hong-Liu Jiang; Kwok-Ho Lam; Zhi-Peng Hu; Zhi-Jie Liu; Hua-Ying Wang; Yong-Yu Yang; Omirserik Baigenzhenov; Ahmad Hosseini-Bandegharaei; Fu-An He (Environmental Science and Pollution Research, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

A systematical review on ethnobotanical, phytochemical and pharmacological aspects of Dendrobium nobile Lindl. - Qian Zhang; Xiujuan Fu; Hao Liu; Yangxi Chen; Siwei Chen; Hong Niu; Yu Luo; Hui Lei; Dan Zhang (Phytochemistry Reviews, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Rayleigh surface wave inversion based on an improved Archimedes optimization algorithm - Zhen-An Yao; Ren Wang; Fu Yu; Long-Feng Chen; Hong-Xing Li; Xiang-Teng Wang; Pan Wang (Applied Geophysics, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Evidence of aircraft activity impact on local air quality: A study in the context of uncommon airport operation - Hao Xu; Kai Xiao; Jun Pan; Qingyan Fu; Xiaodong Wei; Junrui Zhou; Yamei Yu; Xue Hu; Huarui Ren; Jinping Cheng; Shitao Peng; Ningning Hong; et al. (Journal of Environmental Sciences, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Peroxymonosulfate activation for effective atrazine degradation over a 3D cobalt-MOF: Performance and mechanism - Ya Li; Fei Wang; Xueying Ren; Peng Wang; Fu-Xue Wang; Hong-Yu Chu; Shijie Gao; Chong-Chen Wang (Journal of Environmental Chemical Engineering, 2023)

Chronic restraint stress–induced depression-like behavior is mediated by upregulation of melanopsin expression in C57BL/6 mice retina - Yingmei Fu; Shanshan Liu; Yigang Dong; Yixia Gan; Xiaoyun Guo; Hongmei Liu; Qingqing Xu; Ruixue Yuan; Ailing Ning; Wu Hong; Yanmin Peng; Shunying Yu (Psychopharmacology, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

The content and diversity of carotenoids associated with high-altitude adaptation in Tibetan peach fruit - Weikang Zheng; Shiqi Yu; Wang Zhang; Shanshan Zhang; Jialing Fu; Hong Ying; Gesang Pingcuo; Shengjun Liu; Fan Zhao; Qingjiang Wu; Qiang Xu; Zhaocheng Ma; et al. (Food Chemistry, 2023)

Efficient enrichment of iodine by supported ionic liquid with three effective adsorption sites: Heteroatoms, fused aromatic rings and ionic bond - Yu-Qin Xiang; Yuan-Hao Wang; Hao Chen; Jie Fu; Qiu-Hong Zhu; Xiao-Lan Yang; Xin-Hong Xu; Song Qin; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Carbon capture and storage technology by steel-making slags: Recent progress and future challenges - Yingyi Zhang; Laihao Yu; Kunkun Cui; Hong Wang; Tao Fu (Chemical Engineering Journal, 2023)

Lysobacter lactosilyticus sp. nov., a Novel β-Galactosidase Producing Bacterial Strain Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Yu-Huan Wang; Hong-Xing Yang; Shao-Chuang Chuang; Chun-Fu Zhou; Xing Yu; Hao Zhang (Current Microbiology, 2023)

Effects of the probability of pulse-like ground motions on landslide susceptibility assessment in near-fault areas - Jing Liu; Hai-ying Fu; Ying-bin Zhang; Pei-yi Xu; Run-dan Hao; Hai-hong Yu; Yun-yong He; Hong-yan Deng; Lu Zheng (Journal of Mountain Science, 2023)

Mass movement of a long-runout catastrophic landslide on Aug. 21, 2020, in Hanyuan County of China - Xing-Yu Yuan; Zheng-Feng Chen; Wen-Xi Fu; Yue Liu; Hong-Fu Zhou; Fei Ye (Bulletin of Engineering Geology and the Environment, 2022)

Dietary Curcumin Supplementation Enhanced Ammonia Nitrogen Stress Tolerance in Greater Amberjack (Seriola dumerili): Growth, Serum Biochemistry and Expression of Stress-Related Genes - Jiawei Hong; Zhengyi Fu; Jing Hu; Shengjie Zhou; Gang Yu; Zhenhua Ma (Journal of Marine Science and Engineering, 2022)
This study was conducted to determine whether curcumin has a positive effect in greater amberjack (Seriola dumerili), especially the ammonia nitrogen stress tolerance ability. The results showed that the stress recovery process of digestive enzymes amylase and trypsin, as well as absorptive enzymes Na+/K+-ATPase, γ-GT and CK, was accelerated. Lysozyme activity increased in the fish fortified with both curcumin diets. Aspartate aminotransferase activity restriction was activated at a low curcumin level. However, alanine aminotransferase activity restriction happened only at 0.02% dietary curcumin. Facilitation of lipid metabolism by curcumin was very clear, as triglyceride and total cholesterol content was basically maintained at the original level or even showed a slight decrease after recovery. HSP70 and HSP90 genes were not evidently stimulated to express in liver, kidney and spleen tissues. In addition, curcumin showed its inhibition capacity on IL1β and IFN-γ and a promoting effect on TGF-β1. The expression of NF-κB1 decreased in a higher degree in fish fed with 0.02% dietary curcumin, while 0.01% dietary curcumin accelerated the recovery pace of C3 and lgT after stress. This study showed that dietary curcumin supplementation can enhance ammonia nitrogen stress tolerance in greater amberjack, and its application prospect can be confirmed.

mTORC1/C2 regulate spermatogenesis in Eriocheir sinensis via alterations in the actin filament network and cell junctions - Zhen-Fang Li; Shuang-Li Hao; Lan-Min Wang; Hong-Yu Qi; Jia-Ming Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2022)

A histological study of vascular wall resident stem cells in venous malformations - Hou-Fu Xia; Wen-Qiang Lai; Gao-Hong Chen; Ye Li; Qi-Hui Xie; Yu-Lin Jia; Gang Chen; Yi-Fang Zhao (Cell and Tissue Research, 2022)

Comparative Methylome Analysis Reveals Epigenetic Signatures Associated with Growth and Shell Color in the Pacific Oyster, Crassostrea gigas - Chao Tan; Chenyu Shi; Yin Li; Wen Teng; Yongjing Li; Huiru Fu; Liting Ren; Hong Yu; Qi Li; Shikai Liu (Marine Biotechnology, 2022)

Phosphorus fractionation and adsorption characteristics in drinking water reservoir inlet river sediments under human disturbance - Zihao Fu; Zijin Hong; Junling Wei; Yukai Liao; Songlin You; Yifan Wang; Jianjing Lv; Huan Feng; Marek Kolenčík; Xuexiu Chang; Yu Qian (Journal of Soils and Sediments, 2022)

Role of host plants in the suitability and dispersal of an omnivorous predator Arma chinensis Fallou (Hemiptera: Pentatomidae: Asopinae) in a biological control context - Ming-Zhen Pan; Zhi-Xiao Fu; Yu-Yan Li; Hong-Yin Chen; Li-Sheng Zhang; Tong-Xian Liu (Journal of Plant Diseases and Protection, 2022)

Correction to: Publication characteristics, topic trends and knowledge domains of karst ecological restoration: a bibliometric and knowledge mapping analysis from 1991 to 2021 - Kehui Liu; Xiaojin Guan; Guangluan Li; Min Duan; Yi Li; Yanyan Hong; Meimei Lin; Rongxin Fu; Fangming Yu (Plant and Soil, 2022)

Publication characteristics, topic trends and knowledge domains of karst ecological restoration: a bibliometric and knowledge mapping analysis from 1991 to 2021 - Kehui Liu; Xiaojin Guan; Guangluan Li; Min Duan; Yi Li; Yanyan Hong; Meimei Lin; Rongxin Fu; Fangming Yu (Plant and Soil, 2022)

lncRNA BDNF-AS Attenuates Propofol-Induced Apoptosis in HT22 Cells by Modulating the BDNF/TrkB Pathway - Yu-Hai Xu; Yuan Luo; Jiang-Bei Cao; Yan-Hong Liu; Yu-Xiang Song; Xiao-Ying Zhang; Qiang Fu; Wei-Dong Mi; Hao Li (Molecular Neurobiology, 2022)
Propofol is widely used as an intravenous anesthetic in clinical practice. Previous studies have indicated that propofol induces apoptosis in neurons. Brain-derived neurotrophic factor (BDNF), a neurotrophic factor, is associated with neuronal apoptosis. BDNF-AS, a relatively conserved long non-coding RNA, can reverse the transcription of BDNF. This study aimed to investigate the involvement of BDNF-AS in propofol-induced apoptosis in HT22 cells. HT22 cells were treated with various concentrations of propofol at different time points. BDNF-AS was silenced using BDNF-AS-targeting siRNA. TrkB was antagonized by the TrkB inhibitor, ANA-12. Flow cytometry, quantitative reverse-transcription PCR, and western blotting were performed to analyze apoptosis and the expression of genes and proteins, respectively. In propofol-treated HT22 cells, BDNF-AS was upregulated, and BDNF was downregulated in a time- and dose-dependent manner. BDNF-AS downregulation mediated by siRNA mitigated apoptosis, upregulated the expression of Bcl-2, and downregulated the expression of Bax and caspase-3, 7, and 9. ANA-12 downregulated the expression of Bcl-2, upregulated the expression of Bax and caspase-3, 7, and 9, and increased apoptosis. Our study implied that inhibition of BDNF-AS can decrease propofol-induced apoptosis by activating the BDNF/TrkB pathway. Thus, the BDNF-AS-BDNF/TrkB signaling pathway may be a valuable target for treating propofol-induced neurotoxicity.

Integrated metabolism and epigenetic modifications in the macrophages of mice in responses to cold stress - Jingjing Lu; Shoupeng Fu; Jie Dai; Jianwen Hu; Shize Li; Hong Ji; Zhiquan Wang; Jiahong Yu; Jiming Bao; Bin Xu; Jingru Guo; Huanmin Yang (Journal of Zhejiang University-SCIENCE B, 2022)

Predisposition to atrioventricular septal defects may be caused by SOX7 variants that impair interaction with GATA4 - Baolei Li; Zhuoyan Li; Jianping Yang; Nanchao Hong; Lihui Jin; Yuejuan Xu; Qihua Fu; Kun Sun; Yu Yu; Yanan Lu; Sun Chen (Molecular Genetics and Genomics, 2022)

Electrochemical enhancement of high-efficiency wet removal of mercury from flue gas - Nai-jiao Xu; Sen Li; Yu-hong Fu; Zhao-yang Wang; Li-juan Feng; Ji Wang (Environmental Science and Pollution Research, 2022)

Neural circuit control of innate behaviors - Wei Xiao; Zhuo-Lei Jiao; Esra Senol; Jiwei Yao; Miao Zhao; Zheng-Dong Zhao; Xiaowei Chen; Peng Cao; Yu Fu; Zhihua Gao; Wei L. Shen; Xiao-Hong Xu (Science China Life Sciences, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Two new nor -lignans from Selaginella pulvinata (Hook. & Grev.) Maxim and their antihyperglycemic activities - Hua-Wei Lv; Yu-Xia Li; Meng Luo; Jia-Meng Qi; Ze-Fei Fu; Hong-Jian Zhang; Yuan-Qiang Guo; Chu Chu; Han-Bing Li; Ji-Zhong Yan (Natural Product Research, 2022)

Three-dimensional gravity inversion based on 3D U-Net++ - Wang Yu-Feng; Zhang Yu-Jie; Fu Li-Hua; Li Hong-Wei (Applied Geophysics, 2021)

New phenolic acids from the whole herb of Elephantopus scaber Linn. and their anti-inflammatory activity - Lu Fu; Di Pei; Meng Yu; Hai Shang; Jin-Guang Si; Hong-Wu Zhang; Tao Zhang; Zhong-Mei Zou (Natural Product Research, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Holocene sea level trend on the west coast of Bohai Bay, China: reanalysis and standardization - Jianfen Li; Zhiwen Shang; Fu Wang; Yongsheng Chen; Lizhu Tian; Xingyu Jiang; Qian Yu; Hong Wang (Acta Oceanologica Sinica, 2021)

Association between autism spectrum disorder and polymorphisms in genes encoding serotine and dopamine receptors - Jun Liu; Huamei Fu; Jiangying Kong; Hong Yu; Zengyu Zhang (Metabolic Brain Disease, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Spatio-temporal variations of vegetation carbon use efficiency and potential driving meteorological factors in the Yangtze River Basin - Xu-chun Ye; Fu-hong Liu; Zeng-xin Zhang; Chong-yu Xu; Jia Liu (Journal of Mountain Science, 2020)

MESP2 variants contribute to conotruncal heart defects by inhibiting cardiac neural crest cell proliferation - Erge Zhang; Jianping Yang; Yang Liu; Nanchao Hong; Huilin Xie; Qihua Fu; Fen Li; Sun Chen; Yu Yu; Kun Sun (Journal of Molecular Medicine, 2020)

Phytochemical constituents of the pericarps of Illicium difengpi and their anti-inflammatory activity - De-Sheng Ning; Yu-Xia Fu; Li-Yan Peng; Hui Tang; Lian-Chun Li; Xing-De Wu; Yu-Song Huang; Zheng-Hong Pan (Natural Product Research, 2020)

Effects of biochar content on gas diffusion coefficient of soil with different compactness and air contents - Fu Quan Chen; Neng Kai Zhao; Song Feng; Hong Wei Liu; Yu Chuan Liu (Environmental Science and Pollution Research, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

Life cycle environmental and economic assessment of coal seam gas-based electricity generation - Jingmin Hong; Zhaohe Yu; Xing Fu; Jinglan Hong (The International Journal of Life Cycle Assessment, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

The orphan nuclear receptor NUR77 promotes trophoblast invasion at early pregnancy through paracrine placental growth factor - Xiao-Cui Li; Xiang-Jie Yin; Wei Hong; Jie Liu; Feng Jin; Bei-Ying Wang; Yu-Mei Wang; Fu-Ju Tian (Journal of Molecular Medicine, 2019)

Recent research progress in geochemical properties and restoration of heavy metals in contaminated soil by phytoremediation - Jiang-tao Fu; Dong-mei Yu; Xi Chen; Ying Su; Cai-hong Li; Yong-ping Wei (Journal of Mountain Science, 2019)

Interannual and Decadal Changes in Tropospheric Ozone in China and the Associated Chemistry-Climate Interactions: A Review - Yu Fu; Hong Liao; Yang Yang (Advances in Atmospheric Sciences, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Complement Complex C5b-9 Levels Are Associated with the Clinical Outcomes of Acute Ischemic Stroke and Carotid Plaque Stability - Weixin Si; Pingping He; Yi Wang; Yu Fu; Xin Li; Xiaoru Lin; Fenghua Chen; Guodong Cao; Hong Zhang (Translational Stroke Research, 2019)

Mitochondrial Gene Heterogeneity and Population Genetics of Haemaphysalis longicornis (Acari: Ixodidae) in China - Zhong-Bo Li; Yi-Tian Fu; Tian-Yin Cheng; Guo-Min Yao; Qiang-Hong Hou; Fen Li; Yu Zhao; Feng-Cai Zou; Guo-Hua Liu (Acta Parasitologica, 2019)

Two new noroleanane-type triterpenoid saponins from the stems of Stauntonia chinensis - Tong-Tong Feng; Hui-Zheng Fu; Yi-Sheng Yang; Zhi-Qiang Zhou; Mian Dai; Hong-Yu Bi; Dong Wang (Natural Product Research, 2019)

A Highly Selective Fluorescence “Turn on” and Absorbance-Ratiometric Detection of Al3+ in Totally H2O and its Application in Test Paper - Xue-Jiao Sun; Yu-Qing Ma; Hong Fu; Zhi-Yong Xing; Zhi-Gang Sun; Yue Shen; Jin-Long Li (Journal of Fluorescence, 2019)

Interethnic scaling of fraction unbound of a drug in plasma and volume of distribution: an analysis of extrapolation from Caucasians to Chinese - Guo Yu; Hong-Hao Zhou; Qing-Shan Zheng; Guo-Fu Li (European Journal of Clinical Pharmacology, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Conflicting meal recommendations for oral oncology drugs: pose risks to patient care? - Guo Yu; Dan-Na Wu; Yan Gong; Guo-Fu Li; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2018)

Prodigiosin stimulates endoplasmic reticulum stress and induces autophagic cell death in glioblastoma cells - Shu-Yu Cheng; Nan-Fu Chen; Hsiao-Mei Kuo; San-Nan Yang; Chun-Sung Sung; Ping-Jyun Sung; Zhi-Hong Wen; Wu-Fu Chen (Apoptosis, 2018)

OsGLO4 is involved in the formation of iron plaques on surface of rice roots grown under alternative wetting and drying condition - Xiao-Li Yu; Dao-Ming Wu; You-Qiang Fu; Xu-Jian Yang; František Baluška; Hong Shen (Plant and Soil, 2018)

Physical interactions and mutational analysis of MoYpt7 in Magnaporthe oryzae - Lu-yao Huang; Min Wu; Xiao-yun Yu; Lin Li; Fu-cheng Lin; Xiao-hong Liu (Journal of Zhejiang University-SCIENCE B, 2018)

On the ratio of intercellular to ambient CO2 (c i/c a) derived from ecosystem flux - Zheng-Hong Tan; Zhi-Xiang Wu; Alice C. Hughes; Douglas Schaefer; Jiye Zeng; Guo-Yu Lan; Chuang Yang; Zhong-Liang Tao; Bang-Qian Chen; Yao-Hua Tian; Liang Song; Muhammad Tahir Jatoi; et al. (International Journal of Biometeorology, 2017)

Morphological and molecular divergence of Rhipicephalus turanicus tick from Albania and China - Hong-Yu Li; Shan-Shan Zhao; Sándor Hornok; Róbert Farkas; Li-Ping Guo; Chuang-Fu Chen; Ren-Fu Shao; Ji-Zhou Lv; Yuan-Zhi Wang (Experimental and Applied Acarology, 2017)

Fractal dimension and b value of the aftershock sequence of the 2008 M S 8.0 Wenchuan earthquake - WU Hao-Yu; LIU Hong-Fu; XU Wei-Jin; WANG Xia (Natural Hazards, 2017)

Combined iron and magnesium isotope geochemistry of pyroxenite xenoliths from Hannuoba, North China Craton: implications for mantle metasomatism - Xin Miao Zhao; Hui Hui Cao; Xue Mi; Noreen J. Evans; Yu Han Qi; Fang Huang; Hong Fu Zhang (Contributions to Mineralogy and Petrology, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Full-scale field load testing of long drilled shafts with enlarged base constructed in marine sediment - Kai-Fu Liu; Xin-Yu Xie; Zhe Luo; Qing-Hong Hu; Chun-Xia Huang (Marine Georesources & Geotechnology, 2017)

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Erratum to: The Rho kinase inhibitor, fasudil, ameliorates diabetes-induced cardiac dysfunction by improving calcium clearance and actin remodeling - Dongwu Lai; Jing Gao; Xukun Bi; Hong He; Xiaolu Shi; Shaoxiang Weng; Yu Chen; Ying Yang; Yang Ye; Guosheng Fu (Journal of Molecular Medicine, 2017)

The Rho kinase inhibitor, fasudil, ameliorates diabetes-induced cardiac dysfunction by improving calcium clearance and actin remodeling - Dongwu Lai; Jing Gao; Xukun Bi; Hong He; Xiaolu Shi; Shaoxiang Weng; Yu Chen; Ying Yang; Yang Ye; Guosheng Fu (Journal of Molecular Medicine, 2017)

Pollution in the urban soils of Lianyungang, China, evaluated using a pollution index, mobility of heavy metals, and enzymatic activities - Yu LI; Hong-guan LI; Fu-cheng LIU (Environmental Monitoring and Assessment, 2017)

Overexpression of Tau Rescues Nogo-66-Induced Neurite Outgrowth Inhibition In Vitro - Yu-Chao Zuo; Hong-Lian Li; Nan-Xiang Xiong; Jian-Ying Shen; Yi-Zhi Huang; Peng Fu; Hong-Yang Zhao (Neuroscience Bulletin, 2016)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Experimental investigation on the relevance of mechanical properties and porosity of sandstone after hydrochemical erosion - Yan-yan Cai; Jin Yu; Guo-feng Fu; Hong Li (Journal of Mountain Science, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Effect of Lactobacillus Strains on Intestinal Microflora and Mucosa Immunity in Escherichia coli O157:H7-Induced Diarrhea in Mice - Xin Bian; Ting-ting Wang; Min Xu; Smith Etareri Evivie; Guang-Wen Luo; Hong-zhang Liang; Shang-fu Yu; Gui-Cheng Huo (Current Microbiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Synthesis of some new thiazolo[3,2-a]pyrimidine derivatives and screening of their in vitro antibacterial and antitubercular activities - Dong Cai; Zhi-Hua Zhang; Yu Chen; Xin-Jia Yan; Shi-Ti Zhang; Liang-Jing Zou; Li-Hong Meng; Fang Li; Bing-Jie Fu (Medicinal Chemistry Research, 2016)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Isoprenaline induces epithelial–mesenchymal transition in gastric cancer cells - Yan-Jie Lu; Zhi-Jun Geng; Xiao-Yan Sun; Yu-Hong Li; Xiao-Bing Fu; Xiang-Yang Zhao; Bo Wei (Molecular and Cellular Biochemistry, 2015)

Pretreatment with Evans blue, a stimulator of BKCa channels, inhibits compound 48/80-induced shock, systemic inflammation, and mast cell degranulation in the rat - Yaw-Syan Fu; Su-Yu Kuo; Hsuan-Yea Lin; Chun-Lin Chen; Shi-Ying Huang; Zhi-Hong Wen; Kun-Zer Lee; Hung-Tu Huang (Histochemistry and Cell Biology, 2015)

Developmental expression and localization of MHC class I molecules in the human central nervous system - Aifeng Zhang; Hong Yu; Youji He; Yuqing Shen; Ying Zhang; Jiane Liu; Bo Fu; Dan Lv; Fengqin Miao; Jianqiong Zhang (Experimental Brain Research, 2015)

Surface Properties and In Vitro Bioactivity of Fluorapatite/TiO2 Coatings Deposited on Ti Substrates by Nd:YAG Laser Cladding - Chi-Sheng Chien; Yu-Sheng Ko; Tsung-Yuan Kuo; Tze-Yuan Liao; Huan-Chang Lin; Tzer-Min Lee; Ting-Fu Hong (Journal of Medical and Biological Engineering, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Isolation and molecular characterization of two novel HMW-GS genes from Chinese wheat (Triticum aestivum L.) landrace Banjiemang - Hui Shao; Tian-hong Liu; Cong-Fu Ran; Li-Qun Li; Jing Yu; Xin Gao; Xue-Jun Li (Genes & Genomics, 2015)

mTOR ATP-competitive inhibitor INK128 inhibits neuroblastoma growth via blocking mTORC signaling - Huiyuan Zhang; Jun Dou; Yang Yu; Yanling Zhao; Yihui Fan; Jin Cheng; Xin Xu; Wei Liu; Shan Guan; Zhenghu Chen; Yan shi; Roma Patel; et al. (Apoptosis, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Screening and monitoring zearalenone-producing Fusarium species by PCR and zearalenone by monoclonal antibodies in feed from China - Shi-Chun Pei; Yu-Ping Zhen; Jian-Wei Gao; Won-Jong Lee; Hong-Fu Zhang; Cheng Ji; Xuan-Zhe Zhang; Cong Chen (Food Additives & Contaminants Part B-Surveillance, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Clodronate liposomes reduce excessive scar formation in a mouse model of burn injury by reducing collagen deposition and TGF-β1 expression - Shao-wei Lu; Xing-mei Zhang; Hong-min Luo; Yu-cai Fu; Ming-yan Xu; Shi-jie Tang (Molecular Biology Reports, 2014)

Epigallocatechin-3-gallate induces apoptosis, inhibits proliferation and decreases invasion of glioma cell - Hong Li; Zhe Li; Ya-Ming Xu; Yue Wu; Kang-Kang Yu; Can Zhang; Yong-Hua Ji; Gang Ding; Fu-Xue Chen (Neuroscience Bulletin, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

Celastrol exerts synergistic effects with PHA-665752 and inhibits tumor growth of c-Met-deficient hepatocellular carcinoma in vivo - Hong-Lei Jiang; Jun-Zhe Jin; Dan Wu; Dong Xu; Guo-Fu Lin; Hao Yu; Dong-Yan Ma; Jian Liang (Molecular Biology Reports, 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Development and identification of a wheat-Leymus mollis multiple alien substitution line - Ji-Xin Zhao; Wan-Li Du; Jun Wu; Xue-Ni Cheng; Yang Gao; Yu-Hui Pang; Xin-Hong Chen; Shu-Hui Liu; Qun-Hui Yang; Jie Fu (Euphytica, 2013)

The analysis on IP signals in TEM response based on SVD - Chuan-Tao Yu; Hong-Fu Liu; Xin-Jun Zhang; De-Yi Yang; Zi-Hong Li (Applied Geophysics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

The contribution of intersubspecific hybridization to the breeding of super-high-yielding japonica rice in northeast China - Jian Sun; Di Liu; Jia-Yu Wang; Dian-Rong Ma; Liang Tang; Hong Gao; Zheng-Jin Xu; Wen-Fu Chen (Theoretical and Applied Genetics, 2012)

Polycyclic aromatic hydrocarbons in animal-based foods from Shanghai: bioaccessibility and dietary exposure - Ying-Xin Yu; Liang Chen; Dan Yang; Yu-Ping Pang; Shao-Huan Zhang; Xin-Yu Zhang; Zhi-Qiang Yu; Ming-Hong Wu; Jia-Mo Fu (Food Additives & Contaminants: Part A, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

17beta-estradiol attenuates pressure overload-induced myocardial hypertrophy through regulating caveolin-3 protein in ovariectomized female rats - Yu-Hong Cui; Zhi Tan; Xiao-Dong Fu; Qiu-Ling Xiang; Jin-Wen Xu; Ting-Huai Wang (Molecular Biology Reports, 2011)

A review of the pharmacological effects of Arctium lappa (burdock) - Yuk-Shing Chan; Long-Ni Cheng; Jian-Hong Wu; Enoch Chan; Yiu-Wa Kwan; Simon Ming-Yuen Lee; George Pak-Heng Leung; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2011)

Spectroscopic and Molecular Modeling Studies on the Interaction Between a Fluorine-Containing Triazole Derivative and Human Serum Albumin - Jia-Xin Fu; Yu-Shu Ge; Feng-Lei Jiang; Xiao-Hong Sun; Yang Liu; Yi Liu (Biological Trace Element Research, 2011)

PTOV1 is associated with UCH-L1 and in response to estrogen stimuli during the mouse oocyte development - Yu-Wei Yao; Yan Shi; Zhe-Fu Jia; Ya-Hong Jiang; Zheng Gu; Jian Wang; Mohamad Aljofan; Zhao-Gui Sun (Histochemistry and Cell Biology, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

The origin of spongy texture in minerals of mantle xenoliths from the Western Qinling, central China - Ben-Xun Su; Hong-Fu Zhang; Patrick Asamoah Sakyi; Yue-Heng Yang; Ji-Feng Ying; Yan-Jie Tang; Ke-Zhang Qin; Yan Xiao; Xin-Miao Zhao; Qian Mao; Yu-Guang Ma (Contributions to Mineralogy and Petrology, 2011)

A haplotype in the CCR5 gene promoter was associated with the susceptibility to HIV-1 infection in a northern Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Xueyuan Jia; Chao Shen; Yanling Zhao; Yan Jin; Yang Yu; Hong Ling; et al. (Molecular Biology Reports, 2011)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Analysis of Brassica rapa ESTs: gene discovery and expression patterns of AP2/ERF family genes - Jing Zhuang; Ai-Sheng Xiong; Ri-He Peng; Feng Gao; Bo Zhu; Jian Zhang; Xiao-Yan Fu; Xiao-Feng Jin; Jian-Min Chen; Zhen Zhang; Yu-Shan Qiao; Quan-Hong Yao (Molecular Biology Reports, 2010)

Evaluation of genetic diversity in Lentinula edodes strains using RAPD, ISSR and SRAP markers - Li-Zhong Fu; Hong-Yu Zhang; Xue-Qian Wu; Hai-Bo Li; Hai-Long Wei; Qing-Qi Wu; Li-An Wang (World Journal of Microbiology and Biotechnology, 2010)

CCR2-64I allele is associated with the progression of AIDS in a Han Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Yan Jin; Yang Yu; Feng Chen; Jing Bai; Hong Ling; Kaili Wang; et al. (Molecular Biology Reports, 2010)

Studying the Interaction of Pirarubicin with DNA and Determining Pirarubicin in Human Urine Samples: Combining Excitation -Emission Fluorescence Matrices with Second-order Calibration Methods - Hong-Yan Zou; Hai-Long Wu; Yan Zhang; Shu-Fang Li; Jin-Fang Nie; Hai-Yan Fu; Ru-Qin Yu (Journal of Fluorescence, 2009)

Previous pulmonary disease and family cancer history increase the risk of lung cancer among Hong Kong women - Xiao-Rong Wang; Ignatius T. S. Yu; Yuk Lan Chiu; Hong Qiu; Zhenming Fu; William Goggins; Joseph S. K. Au; Lap-Ah Tse; Tze-Wai Wong (Cancer Causes & Control, 2009)

Diammine Dicarboxylic Acid Platinum Enhances Cytotoxicity in Platinum-Resistant Ovarian Cancer Cells through Induction of Apoptosis and S-Phase Cell Arrest - Hong Zheng; Wei Hu; Dongfang Yu; De-Yu Shen; Siqing Fu; John J. Kavanagh; I-Chien Wei; David J. Yang (Pharmaceutical Research, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Association analysis of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Qian-Fu Gan; Lu-Pei Zhang; Jun-Ya Li; Guan-Yu Hou; Heng-De Li; Xue Gao; Hong-Yan Ren; Jin-Bao Chen; Shang-Zhong Xu (Journal of Applied Genetics, 2008)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

The sweet potato sporamin promoter confers high-level phytase expression and improves organic phosphorus acquisition and tuber yield of transgenic potato - Ya-Fang Hong; Chang-Yeu Liu; Kuo-Joan Cheng; Ai-Ling Hour; Min-Tsair Chan; Tung-Hai Tseng; Kai-Yi Chen; Jei-Fu Shaw; Su-May Yu (Plant Molecular Biology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Proteomic analysis of the serum in patients with idiopathic pulmonary arterial hypertension - Min Yu; Xing-xiang Wang; Fu-rong Zhang; Yun-peng Shang; Yu-xi Du; Hong-juan Chen; Jun-zhu Chen (Journal of Zhejiang University-SCIENCE B, 2007)

Promoter trapping in Magnaporthe grisea - Xiao-hong Liu; Jian-ping Lu; Jiao-yu Wang; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Removal of dibutyl phthalate by a staged, vertical-flow constructed wetland - Wen Yu Zhao; Zhen Bin Wu; Qiao Hong Zhou; Shui Ping Cheng; Gui Ping Fu; Feng He (Wetlands, 2004)

The serotonergic system may be involved in the sleep-inducing action of oleamide in rats - Jing-Yu Yang; Chun-Fu Wu; Fang Wang; Hong-Rui Song; Wen-Jun Pan; Yu-Ling Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)

Effect of apple production base on regional water cycle in Weibei upland of the Loess Plateau - Huang Ming-bin; He Fu-hong; Yang Xin-min; Li Yu-shan (Journal of Geographical Sciences, 2001)